Amount of Menstrual Blood and Nutrient Intake with Hemoglobin Level (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
The most influential factor in the anemia is severe menstrual bleeding on each cycle. Heavy menstrual bleeding that can periodically reduce iron stores in the body so that the body has an iron deficiency and lead to anemia. This study aimed to find out the relationship between menstrual blood counts and nutritional intake with hemoglobin (Hb) levels in girls. The study used a cross-sectional design with a sample of 169 young girls in middle school in Banyumas District, Central Java, Indonesia. The amount of menstrual blood was seen using a questionnaire menstrual pictogram. The nutritional intake studied was the intake of protein, fibre, iron, and vitamin C using an FFQ semi-quantitative questionnaire and Hb levels through the insertion of peripheral blood. Data analysis using is chi-square and Fisher exact tests. There was no significant relationship between the amount of menstrual blood with Hb levels (p = 0.54 CI 95% = 0.36-1.74), protein intake (p = 0.26), fibre intake (p = 0.78) and iron intake (p = 0.44). There was a significant relationship between vitamin C intake and Hb levels (p = 0.03 CI 95% = 1.04-4.10). There is a significant relationship between vitamin C intake and hemoglobin levels in young girls.